English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

I asked a question earlier. Can U help again? Thank you!!!!
solve the equation by factoring.

d^2-10d+25=6

2007-08-17 04:52:13 · 8 answers · asked by Eye of the Beholder... 3 in Science & Mathematics Mathematics

8 answers

d^2-10d+25=6
subtract 6 to the other side
so it's d^2-10d+19=0
can't factor, so complete the square

add -19 to both sides
d^2-10d+19-19=-19
d^2-10d=-19
half of -10 and square it and add to both sides
d^2-10d+25=6 <---- lol looks familiar?
square root of both sides
(d-5)(d-5)=radical 6
d-5=radical 6
d = (radical 6) + 5

2007-08-17 04:59:46 · answer #1 · answered by pockethotrod 3 · 0 0

Hey there!

Here's the answer.

d^2-10d+25=6 --> Write the problem.
d^2-10d+19=0 --> Subtract 6 on both sides of the equation.
d^2-10d=-19 --> Subtract 19 on both sides of the equation.
d^2-10d+(10/2)^2=-19+(10/2)^2 --> Use completing the square. The completing the square for x^2+bx is x^2+bx+(b/2)^2.
d^2-10d+25=-19+25 --> Rewrite (10/2)^2 as 25.
(d-5)^2=6 --> Factor out d^2-10d+25 on the left side of the equation. Add -19 and 25 in the right side of the equation.
d-5=±sqrt(6) --> Take the square root on both sides of the equation.
d=5±sqrt(6) Add 5 to both sides of the equation.

So the solutions are 5-sqrt(6) and 5+sqrt(6).

Hope it helps!

2007-08-17 05:14:53 · answer #2 · answered by ? 6 · 0 0

d^2-10d+25=6

The left had side can be factored into a perfect square:
(d - 5)^2 = 6 since (d - 5)^2 = d^2 - 5d - 5d + 25 = d^2 - 10d + 25
So: d - 5 = +/-SQRT(6)
And: d = 5 +/- Sqrt(6)

Or you can do the: d = (-b +/- SQRT(b^2 - 4ac))/2a
Move the 6 to the left hand side and get: d^2-10d+19 = 0
Then a = 1, b = -10 and c = 19

d = (10 +/- SQRT(100 - 76))/2 = (10 +/- 2SQRT(6))
d = 5 +/- SQRT(6)

2007-08-17 05:03:50 · answer #3 · answered by Captain Mephisto 7 · 0 0

d^2-10d+25=6
In order to factor, the equation has to equal zero. So, subtract 6 from both sides.

d^2-10d+19=0

Now, we'll use the quadratic equation because that isn't going to come out evenly.

(-b±√b^2-4ac)/2a
a=1 b= -10 and c=19
[-(-10)±√(-10)^2-4(1)(19)]/2(1)
(10±√100-76)/2
(10±√24)/2
(10±2√6)/2
This gives us two equations.
(10+2√6)/2   and   (10-2√6)/2
reduce.
5+√6 and 5-√6
Those are your roots.

2007-08-17 05:07:12 · answer #4 · answered by Anonymous · 0 0

d^2-10d+25=6
d^2-10d+19=0
use d= -b+/-(squareroot(4ac))/2a
2 answers:
d1=2.55
d2=7.44

2007-08-17 05:06:32 · answer #5 · answered by le newyorkais 2 · 0 0

d^2-10d+25=6
d^2-10d+25-6=0
d^2-10d+21=0
(d-3)*(d-7)=0
d-3=0
d=3
d-7=0
d=7

2007-08-17 05:01:54 · answer #6 · answered by ptolemy862000 4 · 0 0

(d-5)^2 = 6, so d-5 = +/- sqrt(6), and d = 5 + sqrt(6) and 5 - sqrt(6)

2007-08-17 05:01:17 · answer #7 · answered by John V 6 · 0 0

http://consoles.real-incentives.com/?referral=25503

2007-08-17 05:17:53 · answer #8 · answered by Anonymous · 0 0

fedest.com, questions and answers